Pre-Test pan Work Plan sebagai Strategi Pembelajaran Efektif pada Praktikum Bahan Teknik Lanjut Jurusan Pendidikan Teknik Mesin FT UNY - Nurdjito Nurdjito (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
To find the most effective learning strategy for the practicum in the laboratory of materials of the department of Mechanical Engineering Education, Faculty of Engineering, Yogyakarta State University (YSU), a study that aims to determine the effect of applying pre-test and work plan on the learning activities and the achievement of students in the laboratory was conducted. This action research used the purposive random sampling technique. Pre-test and work plan were conducted as the treatment. The data of study was collected through a test to analyse the students’ achievement scores, then they were analyzed using t-test with SPSS. The results of this study indicated that the application of pre-test and work plan in addition to the standard module was proven to be more effective than the  normative learning using the module with t = 3.055 p = 0.003 0.05. The implementation of the pre-test and work plan in addition to the use of standard modules is able to  improve the students’ motivation, independence and readiness to learn as well as the cooperation among the students, therefore the achievement is also improved. The mastery of competencies increased significantly proved by the increasing values of mode 66 to 85 (the experiment), and mean 73.12 into 79.32 (experiment).